Note-taking as communication design: promoting democratic processes. Issue 6 (2nd November 2019) - Reinig, Lydia; Sprain, Leah
ABSTRACT: Whereas notes are ubiquitous to democratic meeting designs, note-taking practices within public participation processes remain taken-for-granted. We argue that note-taking is a communication practice that calls for cultivating expertise and critical reflexivity. Employing Communication as Design (CAD) we analyze communication design logics for note-taking active in public processes and the problems encountered enacting these design logics. CAD analysis illuminates four design logics underpinned by democratic values: notes as summary, data points, quotables, and critical voice. Building from this empirical analysis, democratic note-takers must be sensitive to the need for coordinating design logics to process goals; yet multiple design logics are often necessary to uphold multiple democratic values.